2022
DOI: 10.5937/ratpov59-38811
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of growth, yield and nutritional status of maize (Zea mays L.) through X-ray bombardment of seed

Abstract: Crop improvement faces a lot of challenges ranging from genetic effects of seeds to environmental factors, among others. Therefore, certified hybrid seeds of maize (Oba super II), were exposed to three different doses of X-ray radiation: 3 MGy, 6 MGy, 9 MGy and a control, no exposure (0 MGy) to assess the effect of irradiation on growth performance, grain yield and nutritional status of maize. The field research was conducted in 2016 cropping season at Michael Okpara University of Agriculture, Umudike (latitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The results from [29][30][31][32][33] showed that X-ray significantly affected plant growth (plant height and plant dry matter) and some growth indices (crop growth rate, relative growth rate, absolute growth rate, and leaf area ratio), yield and yield components (number of seeds, weight of seed and grain yield) of maize as well as nutritional value of the crop and leaf growth.…”
Section: Discussionmentioning
confidence: 99%
“…The results from [29][30][31][32][33] showed that X-ray significantly affected plant growth (plant height and plant dry matter) and some growth indices (crop growth rate, relative growth rate, absolute growth rate, and leaf area ratio), yield and yield components (number of seeds, weight of seed and grain yield) of maize as well as nutritional value of the crop and leaf growth.…”
Section: Discussionmentioning
confidence: 99%